Kajian Tingkat Kerusakan Jalan Cipta Karya Kecamatan Tampan Kota Pekanbaru Dengan Pendekatan Pavement Condition Index (PCI) - M. Rahmad Hidayat; Shalahuddin, Muhammad; Djuniati, Sri; Elianora; Saut, Horas; Rurianti, Dwi Visti (Teknik Sipil Universitas Riau, 2025)
Cipta Karya Road in Pekanbaru City has a 2-lane, 2-way undivided road type with a length of about 3.3 kilometers and a lane width of about 5 meters. This road connects Jalan Bersama with Jalan HR. Soebrantas and is located in Tampan District. Based on observations, the surface of Cipta Karya Road in Simpang Baru Village has experienced a lot of damage due to weather, vehicle loads, and other factors. The damage is in the form of patches, holes, cracks, and collapses so that an investigation and assessment of the damage is needed. Factors causing damage include old road age, poor asphalt quality, air flow, and excessive load. The study aims to determine the type of damage and the value of road conditions to determine how to repair it. One assessment using the PCI system shows that there are 7 types of damage and a PCI value of 31 which is included in the bad category. The recommendation is that the government must immediately make repairs.